(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2022)
This paper analyzes the evidence for predation on ostracods observed in Neogene sediments of southwestern Spain. Eighty bored valves were extracted from the analysis of more than 2000 specimens collected in shallow marine to upper bathyal palaeoenvironments. Bored specimens are more abundant in Neogene shallow marine areas, although very high percentages can be obtained in deeper sediments with very low ostracod densities. Two main types of boreholes can be distinguished, being concentrated mainly in the central areas of the valves, and drilled mainly by the gastropods: a) Oichnus paraboloides Bromley, with more of 70% of the total boreholes; and b) Oichnus simplex Bromley. Borehole diameter shows a positive but no significant correlation with the dimensions of the predated valves. Ornamentation seems to be secondary in the predatory selection.